The factors that affecting crude palm oil price in Malaysia / Syafiq Izzuddin Mohamad - Mohamad, Syafiq Izzuddin (2019)
The purpose of this research paper is to investigate the factor that affecting crude palm oil (CPO) price in Malaysia. The independent variables selected to be tested on this study are soybean oil price, exchange rate, volume of export, and volume of production of crude palm oil in Malaysia. The method used to measure the outcome is by using Ordinary Least Square. The statistical tool used to run and analyse the regression analysis is Econometric Views (E-views) software. The time series data with total observation 101 was selected from January 2010 until May 2018. The variables data been selected from reliable sources which are Index Mundi, Malaysian Palm Oil Council (MPOC), and Bank Negara Malaysia. The findings show that the soybean oil has positive and significant relationship with the crude palm oil price. The exchange rate and volume of export have negative and significant relationship between the crude palm oil prices. Meanwhile, the volume of production shows the positive but insignificant relationship with the price of crude palm oil in Malaysia.